2010
DOI: 10.1007/s10895-010-0793-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization Luminiscence Studies and Microbial Activity of Ethylenediamine Ruthenium (II) Complexes with Dipyridophenazine Ligands

Abstract: Three symmetric ligands 7-methyl dipyrido-[3,2-a;2',3'-c]phenazine (dppz-CH(3)), 7-nitro dipyrido-[3,2-a;2',3'-c]phenazine (dppz-NO(2)) and benzo[i]dipyrido-[3,2-a;2',3'-c]phenazine (dppn) and their ruthenium(II) complexes [Ru(en)(2)(L)][ClO(4)](2) (en= ethylenediamine), L= dppz-CH(3), dppz-NO(2) and dppn have been synthesized and characterized by IR, (1)H, (13)C NMR and Mass spectra. The interactions of these complexes with calf thymus DNA have been investigated by spectrophotometric, spectrofluorimetric, cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…ethylenediamine, hydrazone). 68,69 Further support for the binding of the complexes to DNA by intercalation mode was provided by competitive binding experiments with ethidium bromide (EB). This planar compound is non-emissive in phosphate buffer (pH 7.2), due to fluorescence quenching of free EB by solvent molecules, but emits intensely in the presence of DNA as a result of its intercalation between adjacent DNA base pairs.…”
Section: Dna-binding Studies By Absorption and Emission Titrationsmentioning
confidence: 99%
“…ethylenediamine, hydrazone). 68,69 Further support for the binding of the complexes to DNA by intercalation mode was provided by competitive binding experiments with ethidium bromide (EB). This planar compound is non-emissive in phosphate buffer (pH 7.2), due to fluorescence quenching of free EB by solvent molecules, but emits intensely in the presence of DNA as a result of its intercalation between adjacent DNA base pairs.…”
Section: Dna-binding Studies By Absorption and Emission Titrationsmentioning
confidence: 99%
“…In some cases, the extended π-system of dppn may provide stronger binding and intercalation of Ru(II) complexes with DNA than complexes derived from dppz. 49,50 Photocleavage of purified DNA by dppn-containing Ru(II) complexes has been demonstrated owing to its efficient production of 1 O 2 from a dppn-centered 3 ππ* state, combined with its strong DNA binding. 51,52 The complexes [Ru(tpy)(pydppn)] 2+ and [Ru-(pydppn) 2 ] 2+ generated photodynamic DNA−protein and protein cross-links in human fibroblasts, including p53 and proliferating cell nuclear antigen (PCNA) cross-links, consistent with nuclear targeting and DNA oxidation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[3a, 12] Other studies indicated the potential of mixed-ligand ruthenium(II) complexes with ethylenediamine and its derivatives. [13] In contrast to cisplatin, which is known to form preferably intrastrand cross-links between adjacent guanine residues of DNA, [14] ruthenium am(m)ine complexes favor interstrand cross-link formation, probably due to the steric hindrance of the octahedrally configured ruthenium center as opposed to the less crowded square-planar coordination geometry of Pt II . [3a] Although the complexes exhibited very good anticancer activity in primary tumors, low solubility prevented Abstract: With the aim of systematically studying fundamental structure-activity relationships as a basis for the development of Ru II arene complexes (arene = p-cymene or biphenyl) bearing mono-, bi-, or tridentate am(m)ine ligands as anticancer agents, a series of ammine, ethylenediamine, and dieth-A C H T U N G T R E N N U N G ylenetriamine complexes were prepared by different synthetic routes.…”
Section: Introductionmentioning
confidence: 99%